Practical Ways Internalization Tematik by Students in Learning Through Peer Teaching in PGSD FKIP at Tanjungpura University - Tahmid Sabri (STKIP Singkawang, 2017)
A practical way internalize value on elementary school children is very strategic, this study aims to provide the best solution. The method used descriptive through class actions done by the students in a way peer teaching. The findings showed that the Internalization of learning design can practically be done well. Application of learning can be applied Effectively, seen from the way of practicality Internalization in learning and provide a significant positive impact on personality value on individual students toward the creation of Piety, noble, intelligent, skilled, creative, discipline, independence, responsibility and democratic, this achievement can not be separated from the various constraints experienced by teachers, but can be Overcome, so that the meaningfulness of students in learning remains created. This study is expected to be the authorized capital on the development of thematic learning in primary school.